MODERATION OF WORK ENVIRONMENT ON THE INFLUENCE OF WORK DISCIPLINE AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE (A STUDY OF EMPLOYEES OF THE PATI DISTRICT TRANSPORTATION SERVICE) - Sasi Handajani; Endang Tjahjaningsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The Pati Regency Transportation Service is a public-sector agency responsible for traffic management, public transportation services, transport-safety supervision, and the development of transport facilities and infrastructure. Achieving these mandates depends on employee performance. This paper examines the moderating role of the work environment in the links between work discipline, organizational commitment, and employee performance. Data were collected through a quantitative census survey and analyzed in SPSS using descriptive analysis and regression with interaction terms. The findings suggest that work discipline is associated with higher performance, organizational commitment does not show the anticipated positive contribution, and the work environment conditions both relationships.